Tactile temporal offset cues reduce visual representational momentum - Merz, S; Frings, C; Spence, C (Springer, 2021)
The perception of dynamic objects is sometimes biased. For example, localizing a moving object after it has disappeared results in a perceptual shift in the direction of motion, a bias known as representational momentum. We investigated whether the temporal characteristics of an irrelevant, spatially uninformative vibrotactile stimulus bias the perceived location of a visual target. In two visuotactile experiments, participants judged the final location of a dynamic, visual target. Simultaneously, a continuous (starting with the onset of the visual target, Experiments 1 and 2) or brief (33-ms stimulation, Experiment 2) vibrotactile stimulus (at the palm of participant's hands) was presented, and the offset disparity between the visual target and tactile stimulation was systematically varied. The results indicate a cross-modal influence of tactile stimulation on the perceived final location of the visual target. Closer inspection of the nature of this cross-modal influence, observed here for the first time, reveals that the vibrotactile stimulus was likely just taken as a temporal cue regarding the offset of the visual target, but no strong interaction and combined processing of the two stimuli occurred. The present results are related to similar cross-modal temporal illusions and current accounts of multisensory perception, integration, and cross-modal facilitation.